The Ambushed Spirit: Perspective, Violence and Downsizing - Daniela Truty (Adult Education Research Conference, 2002)
The purpose of this study was to investigate downsizing from the perspective of the person who was separated from the job, and to explore its connection to violence and peace studies. Findings suggest that experiences varied according to context and point of view and that downsizing was often a violative.